2006
DOI: 10.2337/db05-1423
|View full text |Cite
|
Sign up to set email alerts
|

The 30-Year Natural History of Type 1 Diabetes Complications

Abstract: Declining incidences in Europe of overt nephropathy, proliferative retinopathy, and mortality in type 1 diabetes have recently been reported. However, comparable data for the U.S. and trend data for neuropathy and macrovascular complications are lacking. These issues are addressed using the prospective observational Pittsburgh Epidemiology of Childhood-Onset Diabetes Complications Study. Participants were stratified into five cohorts by diagnosis year: 1950 -1959, 1960 -1964, 1965-1969, 1970 -1974, and 1975-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
303
3
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 448 publications
(329 citation statements)
references
References 41 publications
7
303
3
16
Order By: Relevance
“…Over the past few years, the efforts to improve metabolic control in childhood diabetes have probably contributed to the decreasing prevalence of diabetic complications [1][2][3]. Particularly since the strong proof provided by the Diabetes Control and Complications Trial (DCCT) [4], attempts to keep HbA 1c below the proposed threshold value have been adopted by most clinicians, including those in paediatric clinics, especially as it has been shown that, as early as in the first years of type 1 diabetes, metabolic control has an impact on markers of late complications [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the efforts to improve metabolic control in childhood diabetes have probably contributed to the decreasing prevalence of diabetic complications [1][2][3]. Particularly since the strong proof provided by the Diabetes Control and Complications Trial (DCCT) [4], attempts to keep HbA 1c below the proposed threshold value have been adopted by most clinicians, including those in paediatric clinics, especially as it has been shown that, as early as in the first years of type 1 diabetes, metabolic control has an impact on markers of late complications [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…If this interpretation is correct, we may need to reconsider the widespread clinical assumption that improved glucose control and antihypertensive therapy have converted the malignant angiopathy of early-onset diabetes into something more benign. They may simply have shifted the survival curve to the right, as suggested by at least one study [25].…”
Section: Nephropathy: the Scylla Of Diabetesmentioning
confidence: 97%
“…Nor could proteinuria ever be considered benign, for its mortality was 100% by 24 years, and uraemia developed to an equal extent in those who died before or after 10 years of proteinuria [20]. Furthermore, the bell-shaped pattern of incidence reported from Denmark [20] may not be universal, and the Pittsburgh Study showed a sustained increase in the incidence of nephropathy over the first 35 years of diabetes [25].…”
Section: Nephropathy: the Scylla Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Microvascular complications remain common in type 1 diabetes [1,2]. Identifying early biomarkers of diabetic peripheral neuropathy (DPN), diabetic nephropathy (DN) and diabetic retinopathy (DR) will allow the earlier implementation of treatment and support the development of new treatment modalities.…”
Section: Introductionmentioning
confidence: 99%